ANALISA PEMASANGAN FILTER HYBRID TERHADAP BEBAN-BEBAN NON LINIER PADA BLUE POINT BAY VILLA DAN SPA - I Wayan Dedy Setiawan; I Wayan Rinas; Antonius Ibi Weking (Program Studi Teknik Elektro UNUD, 2018)
A previous review of harmonic analyzes has been conducted at The Blue Point Bay Villa & Spa hotel, where there are many high non linear loads, resulting in harmonic distortions that have an impact on power losses. The current harmonic content of the electricity system at The Blue Point Bay Villa & Spa hotel does not meet the IEEE 519-1992 standard which results in decreased power quality. This research analyzes the steps of installing high-pass hybrid filter type to reduce harmonic distortion, analyze power losses using ETAP software. Analysis is performed before and after the installation of hybrid filters. The analysis result of hybrid filter simulation can reduce harmonic distortion with THDi value at SDP1 equal to 6,42%, SDP2 equal to 6,41%, SDP3 equal to 6,42%, SDP4 6,41%, and SDP5 6,42%. THDv value simulation results on all SDP before installation of hybrid filter that is 8.80% and after installation of hybrid filter that is 0,13%.